Hilyetü’l-evliyâʾ ve tabakâtü’l-asfiyâ’ - 880-01 Ebû Nuaym el-İsfahânî, 948-1038. (Beyrut)
10 cilt (1. c. 399 sayfa ; 2. c. 400 sayfa ; 3. c. 384 sayfa ; 4. c. 395 sayfa ; 5. c. 400 sayfa ; 6. c. 400 sayfa ; 7. c. 400 sayfa ; 8. c. 400 sayfa ; 9. c. 400 sayfa ; 10. c. 415 sayfa)